2020
DOI: 10.1096/fj.201902118r
|View full text |Cite
|
Sign up to set email alerts
|

In vivo ectopic Ngn1 and Neurod1 convert neonatal cochlear glial cells into spiral ganglion neurons

Abstract: Damage or degeneration of inner ear spiral ganglion neurons (SGNs) causes hearing impairment. Previous in vitro studies indicate that cochlear glial cells can be reprogrammed into SGNs, however, it remains unknown whether this can occur in vivo. Here, we show that neonatal glial cells can be converted, in vivo, into SGNs (defined as new SGNs) by simultaneous induction of Neurog1 (Ngn1) and Neurod1. New SGNs express SGN markers, Tuj1, Map2, Prox1, Mafb and Gata3, and reduce glial cell marker Sox10 and Scn7a. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The genetic constructs were designed such that upon Cre-mediated recombination, Tdtomato and Ikzf2 would be translated, initially together from the same polycistronic mRNA, and subsequently cleaved by the 2A peptide ( Li et al, 2020a ); and once triggered, expression of Ikzf2 and Tdtomato would be permanent, enabling genetic fate-mapping analysis at single-cell resolution. Thus, this construct, when used in conjunction with a SC-specific Cre-driver, would readily allow us to distinguish potential new OHCs (Tdtomato+) derived from adult cochlear SCs (primarily PCs and DCs in this study) from endogenous OHCs (Tdtomato−).…”
Section: Resultsmentioning
confidence: 99%
“…The genetic constructs were designed such that upon Cre-mediated recombination, Tdtomato and Ikzf2 would be translated, initially together from the same polycistronic mRNA, and subsequently cleaved by the 2A peptide ( Li et al, 2020a ); and once triggered, expression of Ikzf2 and Tdtomato would be permanent, enabling genetic fate-mapping analysis at single-cell resolution. Thus, this construct, when used in conjunction with a SC-specific Cre-driver, would readily allow us to distinguish potential new OHCs (Tdtomato+) derived from adult cochlear SCs (primarily PCs and DCs in this study) from endogenous OHCs (Tdtomato−).…”
Section: Resultsmentioning
confidence: 99%
“…Heterozygous and homozygous Rosa26-CAG-LSL-Ikzf2 mice were healthy and fertile, and did not display any apparent phenotypes. Upon Cre-mediated recombination, Tdtomato and Ikzf2 were initially translated together from the same polycistronic mRNA, and subsequently separated by the 2A peptide (Li et al, 2020b). Once triggered, the expression of Ikzf2 and Tdtomato was permanent, which enabled genetic fate-mapping analysis at single-cell resolution.…”
Section: Resultsmentioning
confidence: 99%
“…However, a direct comparison of glial subpopulations is lacking and the iNs did not appear to mature as SGNs. Importantly, two groups recently reported that iNs can be generated from Plp1 + glial cell by Ng1/Nd1 or Lin28 overexpression in vivo post-SGN injury, and that iNs expressed both pan-neuronal and SGN markers ( Kempfle et al, 2020 ; Li X. et al, 2020 ). However, the efficiency of neuronal conversion and neuronal maturity is still limited.…”
Section: Discussionmentioning
confidence: 99%